The function of the stylistic context in the texts of reasoning (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
Contextual variability from different sides is considered, different types of contexts are distinguished. It is emphasized that the concept of the context as a property of the entire language system and the form of its existence determines the need to take into account the genre of the work and its pragmatic essence.This article analyzes the texts of English prose in the second half of the 17 th century. These are texts-reasonings presented by different genres: essays, sermons, meditations, diaries. This allows us to come up with generalizations at the level of typology of texts, supplementing both the stylistics and the theory of the text with new observations on previously unexamined materials.The article concludes that if in the contextual analysis it is necessary to establish a reference minimum that allows one to identify one of several possible values, then in the stylistic context it is desirable to identify not a minimum, but a possible maximum of contextual links, since the compression of information in the text rests on the ability of the word to act in others values causing additional associations. The implementation of stylistically relative meanings of words in this context is possible only when taking into account the entire semantic range generated by the vertical context.It is concluded that the word-image can arise only in a context that by its entire mechanism actively keeps this imagery at the level of the necessary denoter, allowing fluctuations and detachments from the marked boundaries of direct values to the associatively prepared microcontexts. Analysis of the functioning of the word in two different types of context reveals that in the texts-reasoning the aspect of the rhetorical expressiveness of the verbal in the formulation of thought has its own peculiarities. The word is more firmly fused with the thought, its meaning and image, from which the analytic is born is much stronger than in the description texts, and this is due to the manifestation of the fact of speech with all the special forms of its construction.